ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU IMPULSE BUYING PADA OUTLET-OUTLET PRODUK FASHIONdi ROYAL PLAZA SURABAYA - Nusaputri, Syariy; Mulyati, Awin; Maruta, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2015)
The background of this research with the advent of globalization brought into the rapidly growing modern retail and ultimately make the increasing competition in the modern retail industry in Indonesia. There are interesting of consumer behavior in modern retail, most shoppers in modern retail stores in major cities such as Jakarta, Bandung and Surabaya experienced impulse buying (unplanned purchase) when shopping. This study tried to determine what factors are causing consumers to impulse buying. This study uses three independent variables namely Product Characteristics (X1), Characteristics of Marketing (X2), Characteristics of Consumers (X3), and impulse buying as the dependent variable (Y).After a literature review and hypothesis formulation, data were collected through questionnaires distributed method to 100 shoppers in outlets fashion products at the Royal Plaza Surabaya who had not planned to make a purchase using purposive sampling.Based on the results of the analysis conducted found that, three independent variables significantly influence the dependent. Variable product characteristics positive effect of 0.282 with a significance level of 0.000, variable marketing characteristics positive effect of 0.566 with a significance level of 0.000, the variable characteristics of a positive effect of 0,142 consumers with a significance level of 0.012. The third variable characteristic of Marketing is the most dominant variable among other variables.Â Â Keywords:Product characteristics, Characteristics marketingl,impulse buying,